TINJAUAN YURIDIS TINDAK PIDANA KESUSILAAN DI MUKA UMUM OLEH MILITER (PUTUSAN NO 07–K/PM.III-12/AD/I/2020) : Juridical Review of Criminal Acts of Public Decency by the Military (Decision No. 07-K/PM.III-12/AD/I/2020) - Muhammad Haritza Ardeanny Kurniawan; Aprima Suar (Faculty of Law, Universitas Trisakti, 2024)
The crime of adultery committed by the military is tried using general criminal provisions because adultery carried out militarily, as in the case of Decision No. 07-K/PM.III-12/AD/I/2020. The formulation of the problem in question is are the actions of the defendant in the crime of adultery by Article 281 paragraph (1) of the Criminal Code or Article 284 paragraph (1) of the Criminal Code? (Decision No. 07-K/PM.III-12/AD/I/2020) and how is the punishment of the military for committing the crime of adultery? (Decision No. 07-K/PM.III-12/AD/I/2020). This research was conducted using normative juridical research type with descriptive-analytical nature with secondary data which was analyzed qualitatively, followingand a conclusion was drawn based on deductive logic. The results of the research show that the actions of the defendant are not in accordance with the provisions of Article 281 paragraph (1) of the Criminal Code because the actions of the perpetrator should be included in the Crime of Adultery based on Article 284 paragraph (1) to 2a of the Criminal Code and the punishment given to the perpetrator is not appropriate which the defendant should be declared free from all legal charges (Onslaag van Alle Recht Vervolging).